2022
DOI: 10.3390/nu14071431
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Evidences of Calorie Restriction and Intermittent Fasting for Neuroprotection in Traumatic Brain Injury Animal Models: A Review of the Literature

Abstract: It has widely been accepted that food restriction (FR) without malnutrition has multiple health benefits. Various calorie restriction (CR) and intermittent fasting (IF) regimens have recently been reported to exert neuroprotective effects in traumatic brain injury (TBI) through variable mechanisms. However, the evidence connecting CR or IF to neuroprotection in TBI as well as current issues remaining in this research field have yet to be reviewed in literature. The objective of our review was therefore to weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 98 publications
(113 reference statements)
0
11
0
Order By: Relevance
“…Thus, autophagy activation is recently emerging as a hot topic to study neuroprotective mechanisms in chronic retinal neurodegenerative disorders (Kaarniranta et al, 2022). Similarly, given the parallelism between traumatic and chronic degenerative conditions, the activation of autophagy in the course of traumatic CNS injury is thought to produce a strong activation to elicit functional and anatomical recovery (Movahedpour et al, 2022;Zhang et al, 2022;Filippone et al, 2022;Xu et al, 2022;Kanno et al, 2022). This is partly based on the induction of stem cells (Xu et al, 2021;Maiti et al, 2019;Ceccariglia et al, 2020;Hwang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, autophagy activation is recently emerging as a hot topic to study neuroprotective mechanisms in chronic retinal neurodegenerative disorders (Kaarniranta et al, 2022). Similarly, given the parallelism between traumatic and chronic degenerative conditions, the activation of autophagy in the course of traumatic CNS injury is thought to produce a strong activation to elicit functional and anatomical recovery (Movahedpour et al, 2022;Zhang et al, 2022;Filippone et al, 2022;Xu et al, 2022;Kanno et al, 2022). This is partly based on the induction of stem cells (Xu et al, 2021;Maiti et al, 2019;Ceccariglia et al, 2020;Hwang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…4.1 Nutritional strategies: Fasting, phytochemicals, phytomelatonin, and fermented food 4.1.1 Fasting Fasting is an effective way to recover mitochondrial efficiency, and multiple human studies have shown its ability to restore metabolic pathways in people suffering from chronic pathologies. Fasting regimens are promising primary and secondary prevention strategies in patients suffering from metabolic and cardiovascular diseases (Oliveira et al, 2022;Papakonstantinou et al, 2022;Vasim et al, 2022;Zang et al, 2022), pain, inflammation and immune conditions (Feng et al, 2022;Fitzgerald et al, 2022;Parveen and Alhazmi, 2022), cancer (Lv et al, 2014;Marinac et al, 2016;Taucher et al, 2022;Tiwari et al, 2022), and neurological diseases characterized by altered mood, sleep, pain, and cognition (Phillips, 2019;Brocchi et al, 2022;Caron et al, 2022;Feng et al, 2022;Lobo et al, 2022;Xu et al, 2022).…”
Section: Figurementioning
confidence: 99%
“…There is a strong consensus in that IF and CR promote AHN; for example by increasing the number of immature neuroblasts (Dias et al, 2021), increasing the survival of neuronal precursor cells and their differentiation into mature neurons (Lee et al, 2002;Levenson and Rich, 2007;Kaptan et al, 2015;Baik et al, 2020); boost the number of shuttle shaped cells in the subgranular zone, the cell density in CA3 and the number of neurons and glia (Bondolfi et al, 2004;Liu et al, 2017;Mana et al, 2017;Cao et al, 2022;Xu et al, 2022). Only one study evidenced a decreased number of new hippocampal neurons in response to IF (Setel et al, 2022).…”
Section: Caloric Restriction and Intermittent Fastingmentioning
confidence: 99%
“…Several studies highlighted that IF and CR dependent neurogenesis is linked with increased expression of hippocampal NPY (Singh et al, 2015;Cao et al, 2022;Xu et al, 2022) and depends on increased quantities of hippocampal acyl-ghrelin (Kim et al, 2015;Hornsby et al, 2016) and ghrelin receptor (Hornsby et al, 2016). Notably, IF and CR also induced a CREB-dependent increase in SIRT1 and SIRT3 (Pani, 2015;Liu et al, 2019;Baik et al, 2020;Landry and Huang, 2021).…”
Section: Caloric Restriction and Intermittent Fastingmentioning
confidence: 99%